Marriage Italian style [videorecording (DVD)] - De Sica, Vittorio, 1901-1974; Loren, Sophia, 1934-; Mastroianni, Marcello, 1924-1996; Puglisi, Aldo; Lindstrom, Pia; De Filippo, Eduardo, 1900-1984 (New Star Video [distributor], 2005)
"Filumena (Sophia Loren) was working in a brothel when she first met Domenico (Marcello Mastroianni), and has been his mistress ever since. Upon hearing that he plans to marry a much younger woman, Filumena devises a brilliant scheme to convince him that it is her that he should be marrying"--Container.